Des conflits autour de projets d’installations de stockage de déchets : les irréversibilités dans l’usage du droit administratif - Laura Chatel; Perrine Vincent; Jacques Mery; Marta Matias-Mendes (Développement Durable et Territoires)
Emblematic of rejected equipment, sanitary landfills are often the subject of legal disputes within a parallel process to the decision-making approach, and presenting distinctive time frames. The discrepancies observed between a "legal time", rather long, and the « landfill project time », subject to technical and economic constrains implying deadlines, maintains a constant uncertainty about the outcomes of the projects. The reversibility, which is inherent to any recourse to litigation, appears to be an important key to reading the landfills project implementation processes and the associated conflicts, capable to highlight the stakeholder’s ability to adapt their strategies depending on the temporalities involved.